Environmental education in Kvarngärdesskolan, Uppsala - Nguyen, Khoa Minh (2009)
This paper is based on a project I conducted in Kvarngärdesskolan in Uppsala, which focused on the topic of environmental education. In order to fulfill the project, I had interviews with a teacher and a number of ninth grade students. My aim is to investigate the perceptions and opinions of teachers and pupils involving teaching and learning environmental issues at comprehensive school context. The paper describes and discusses about the data of those interviews, the method which I have done as well as the theory used in my interpretation of the materials. The paper ends with some general conclusions, based on the discussion and interpretation part.